A Chimeric Peptide Logic Gate for Orthogonal Stimuli‐Triggered Precise Tumor Therapy. (10th October 2018) - Dai, Xinxin; Han, Kai; Ma, Zhaoyu; Han, Heyou
Abstract: The precise recognition of tumor tissue is the key challenge that hinders successful clinical translation of drug delivery systems. Herein, a tumor extracellular matrix orthogonal stimuli‐responsive chimeric peptide is developed for logic gate controlled tumor recognition and photodynamic therapy. In vitro studies show that the negatively charged chimeric peptide is sensitive to two typical tumor hallmarks, i.e., mild acidity and matrix metalloproteinase 2 (MMP‐2) simultaneously. Consequently, the chimeric peptide can undergo charge reversal from negative charge to positive charge in tumor, accelerating the cellular uptake. Specifically, the enhanced cellular uptake of chimeric peptide can be activated efficiently only in the presence of both acidity and MMP‐2, endowing chimeric peptide with highly specific tumor therapy both in vitro and in vivo. This chimeric peptide based "AND" logic gate should show great potential in precise tumor therapy. Abstract : A tumor extracellular matrix orthogonal stimuli‐responsive chimeric peptide is developed for logic gate controlled tumor recognition and photodynamic therapy. Different from traditional "OR" and "AND" logic gates, this peptide undergoes surface charge reversal only under orthogonal stimuli (tumor hallmarks), realizing precise tumor therapy both in vitro and in vivo.